IMPLEMENTASI STRATEGI DIGITAL MARKETING DALAM MENINGKATKAN KINERJA PERUSAHAAN (Studi Kasus Pada Perusahaan Semeloto.id di Sumbawa) - Kristiana; Muhammad Nur Fietroh (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2021)
This research is the result of descriptive qualitative research which aims to answer how the implementation of digital marketing strategies in improving company performance is carried out by the Semeloto.id company in marketing or promotion through digital marketing to attract consumers who actively use social media. The determination of informants is based on the criteria formulated by the researcher with certain considerations or criteria. In the selection of informants for this study, the owner of the Semeloto.id company was Yunita Lestari. Data collection was carried out by interview, observation, account observation, and documentation on business management and marketing in the city of Mataram. From the results of this study, the implementation of Semeloto.id's digital marketing strategy in improving company performance, focusing through digital marketing, because promotion through digital marketing is more efficient and reduces costs and puts forward the form of promotion that is trending and is able to attract customer attention, and one of the things that interesting thing done by Semeloto.id, namely uploading content related to Semeloto.id products. From Semeloto.id's digital marketing style, it has a positive impact in improving company performance. With the strategies that have been implemented by Semeloto.id, it is able to attract potential consumers to buy Semeloto.id products and this can improve company performance. From the results of the above research, it is hoped that the implementation of the company's digital marketing strategy, Semeloto.id, will always have innovation and expand the market globally so that it can improve the progress of the companies and brands that have been built.